2017
DOI: 10.1146/annurev-immunol-110416-120628
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of the JAK/STAT Pathway in T Cell Lymphoma Pathogenesis: Implications for Immunotherapy

Abstract: Common gamma receptor–dependent cytokines and their JAK/STAT pathways play pivotal roles in T cell immunity. Abnormal activation of this system was pervasive in diverse T cell malignancies assessed by pSTAT3/pSTAT5 phosphorylation. Activating mutations were described in some but not all cases. JAK1 and STAT3 were required for proliferation and survival of these T cell lines whether or not JAKs or STATs were mutated. Activating JAK and STAT mutations were not sufficient to initiate leukemic cell proliferation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 93 publications
1
120
0
Order By: Relevance
“…Importantly, the functional analysis of 1 of these 5 genes (RGD, leucine-rich repeat, tropomodulin and prolinerich containing protein [RLTPR]) further highlights the involvement of the CD80/ CD86-CD28 axis in MF/SS, already evident from previous studies, and illustrates the role of TCR signaling as a codriver of MF/SS development. Analogous to other T-cell malignancy models, where JAK/STAT mutations initiate tumor cell proliferation only in the presence of cytokine signaling, 9 RLTPR mutations alone were not sufficient to induce transcriptional programs associated with T-cell activation but potentiated .30-fold the effects of TCR signaling. Thus, the functional effect of mutations affecting downstream components of TCR or cytokine signaling needs to be tested and interpreted in the context of the appropriate microenvironment.…”
mentioning
confidence: 82%
“…Importantly, the functional analysis of 1 of these 5 genes (RGD, leucine-rich repeat, tropomodulin and prolinerich containing protein [RLTPR]) further highlights the involvement of the CD80/ CD86-CD28 axis in MF/SS, already evident from previous studies, and illustrates the role of TCR signaling as a codriver of MF/SS development. Analogous to other T-cell malignancy models, where JAK/STAT mutations initiate tumor cell proliferation only in the presence of cytokine signaling, 9 RLTPR mutations alone were not sufficient to induce transcriptional programs associated with T-cell activation but potentiated .30-fold the effects of TCR signaling. Thus, the functional effect of mutations affecting downstream components of TCR or cytokine signaling needs to be tested and interpreted in the context of the appropriate microenvironment.…”
mentioning
confidence: 82%
“…These observations were a strong rationale for the development of the JAK1/JAK2 inhibitor ruxolitinib (Figure 3), and the clinical trials that led to its approval by the FDA in 2011 showed that JAK inhibition was not only possible, but safe and effective for these indications 22,23 . Indeed, the JAK-STAT pathway is constitutively activated in many cancers 1324 , which has led to the initiation of multiple trials using jakinibs in hematological and solid tumours, including trials in which multiple kinase inhibitors are used in combination (e.g. NCT02912754).…”
Section: Can Jaks Be Successfully Specifically and Safely Targeted?mentioning
confidence: 99%
“…Furthermore, various mechanisms contribute to the constitutive activation of the JAK/STAT pathway that is observed in nearly all T‐cell lymphomas subtypes; autocrine and paracrine interactions involving either cytokines or their cognate receptors have been consistently reported, while a minority of cases showed a range of mutational events, including fusion genes, involving either STAT proteins as STAT3 and STAT5B or members of the JAK family, mostly JAK1 or JAK3 . In detail, such activating mutations are prevalent among aggressive and/or extranodal lymphoma subtypes, such as natural killer (NK)/T‐cell neoplasms and hepatosplenic T‐cell lymphomas …”
Section: Jak2 At the Crossroad Between Myeloid And Lymphoid Disordersmentioning
confidence: 99%